Розроблення та дослідження ручного віброкотка для ущільнення грунтів та дорожніх покриттів - Лютенко, В. Є.; Копитов, А. А. (Техніка будівництва, 2020)
The results of research of work hand vibroroller for ground and pavement compaction are presented. Defines the main design parameters of the manual vibrating compactor. A mathematical model of vibrating compactor with a drive from the electric motor, as well as carried out a pilot study to determine the vibration displacements and vsbration velocities for different velocities for unbalanced shaft and different for unbalanced mass. According to the results of theoretical studies is made the manual vibrating compactor.